Macroeconomics reader - Vane, Howard R., ed.; Snowdon, Brian, ed. (London Routledge, 1997)
A Macroeconomics Reader brings together a collection of key readings in modern macroeconomics, with each article carefully chosen to provide the reader with accessible, non-technical, reflective assessments of various aspects of the subject
Includes Bibliographical References And Index
Keywords: Keynesian economics--Macroeconomics; Economic growth analysis--Macroeconomics; New classical macoeconomics